Arrhythmic storm in the acute coronary care unit. (26th April 2021) - Garcia-Arribas, D; Rosillo, S; Caro, J; Armada, E; Carrion, I; Ferrera, C; Noriega, FJ; Viana, A; Lopez De Sa, E
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Beca para la Formación e Investigación en Cuidados Críticos Cardiológicos concedida por la Asociación de Cardiopatía Isquémica y Cuidados Críticos Cardiológicos de la SEC Introduction: Available data on arrhythmic storm (AS) is usually obtained from retrospective observational studies based on series of patients (pts) with ICD or who undergo ablation. Therefore, selection bias limits the evidence regarding mortality and prognosis of this entity. Purpose/ Methods Describe epidemiological and clinical characteristics, as well as therapeutic strategies and in-hospital mortality as main outcome of pts admitted between 2006 and 2020 for AS in the Acute Cardiac Care Unit (ACCU) of 2 tertiary hospitals in Madrid, Spain. Results: A total of 190 episodes of AS in 169 pts were analysed. Baseline characteristics are depicted in Figure 1. Cardiovascular targeted treatments of pts included: betablockers (68.7%), ACEi or ARB (53.2%), ARNI (6.5%), AA (38.5%), group III antiarrhythmic drugs (27.1%) and digoxin (5.9%). Aetiology of the AS was determined in 68.6% of the episodes: myocardial ischemia 25.1%, STEMI 22.5%, acute myocarditis 0.5%, heart failure or cardiogenic shock 28.8%, infection 11%, Bradycardia and long QT interval 10%, ionic disturbances 6.3%, others 11.5%. Antiarrhythmic drugs used for the acute episode were: amiodarone (73.3%), procainamide (27.2%), sotalol (5.7%), other beta blockers (75.9%), calcium channel blockers (3.1%), quinidine (2.1%). Other therapies were performed as follows: sedative drugs 50.3%, endotracheal intubation 39, 9%, correction of electrolyte disturbances 51.8%, therapeutic hypothermia 13.6%, intravenous temporary pacemaker insertion or ICD reprogramming (9.9%). In 45% of pts coronary angiography was performed, but only 25.7% required revascularization. Vasopressors and inotropic drugs were used in 51% of pts. Regarding mechanical support intra-aortic balloon pump was implanted in 16.2% of episodes, ECMO in 3.7% and other left ventricular assist devices in 3.1%. One patient was transplanted. Ventricular tachycardia (VT) ablation was performed in 38.7% of episodes and its efficiency was 69.4%. Three pts underwent stellate ganglion ablation and surgical sympathectomy, and in one pt sympathectomy alone was performed. ICD was implanted in 23 pts after the AS episode. Survival at discharge was 81.1%. Mortality in STEMI related AS was 44.2%, while in the rest of aetiologies was 6.1%. Mortality among patients with an ICD was 6.3%. Conclusion: Patients with AS requiring admission to an ACCU have predominantly ischemic background (both acute and chronic). Most common therapeutics are beta-blockers, amiodarone, sedation and VT-ablation. In-hospital mortality differs depending on the aetiology being worst in STEMI related AS.